Ciência da Informação e Ciência da Administração: questões epistemológicas e o fenômeno da informação - Alves, José Alexandre da Costa (2008)
Theorical discussion about information phenomenon, based on Information Science and Administrative Science epistemological articulations, mainly according to the new holes of information in organizations, including approaches of the Information Society, the paradigm shifts of “ information regulation” and primarily issues concerning organizational information processing and use. Epistemological approach conducted the research in order to assure theorical articulation. The social sciences paradigms were discussed, in order to approximate Information Science and Administrative Science. The majors theories and epistemological paradigms about these sciences, conducted to an epistemological interdisciplinary discussion between Information Science and Administrative Science concerning the information phenomenon.